The Effect of Director's Remuneration, Audit Fee, and Director's Expertise on Earnings Management with Sales Growth as Moderating Variable - Septiana Indrawati; Dwi Asih Surjandari (The Indonesian Journal of Accounting Research, 2022)
The purpose of this study is to examine the factors that influence earnings management practices in state-owned companies and their subsidiaries listed on the Indonesia Stock Exchange. The samples used in this study were 9 state-owned companies and subsidiaries listed on the IDX for the period 2013-2019, with a total of 63 samples. The analytical tool used to analyze the hypothesis is Eviews 11.0. The results showed that the expertise of the director has a significant positive effect on earnings management. However, director's remuneration and audit fee have no effect on earnings management. Sales growth proved unable to moderate the relationship of director remuneration, audit fees and director's expertise to earnings management. This research has important implications for building informal control over an action that will be taken by the directors through the perspective of religiosity in influencing the behavior and decisions that will be taken by the directors.